Pengembangan E-book Bergambar Untuk Meningkatkan Sikap Sosial Siswa di SMA Negeri 2 Palembang - Putri, Fadilah Syahrani Kesumah (PPSDP Undergraduate Journal of Educational Sciences, 2025)
Students in 21st century education must have a positive social attitude in order to build relationships in social life, especially in sympathy and empathy. 21st century education is characteristically characterized by an emphasis on learning using developments by utilizing technology, education in the era of the 4.0 revolution now because of the internet that can make it easier to learn anytime and anywhere. Based on this, the purpose of the research is to develop a picture e-book as an electronic media in the provision of counseling guidance services to improve students’ social attitudes at SMA Negeri 2 Palembang. The problem in this study is still the low social attitude of students at SMA Negeri 2 Palembang, especially the sympathy and empathy of students and the lack of electronic media in the provision of information services. The research method used is (research and development) with a 3D research model. The population in this study is all students of class X totaling 500 students. The researcher took a sample of 45 subjects of class X students. The data analysis technique uses validity analysis. Based on the results of media expert validation of 93.75%, linguist validation of 81.81% and validation of material experts of 96.15%, the pretest results were 90.77% in the sufficient category and the post test results were 96.37%. It was concluded that the illustrated e-book to improve students’ social attitudes at SMA Negeri 2 Palembang was developed which is feasible to use and can improve students’ social attitudes.